Beyond Access to Nature: Nature-Based Learning, Meaningful Participation, and Outcomes for Children with Disabilities - Asri Wijiastuti; Khofidotur Rofiah; Ima Kurrotun Ainin; Sujarwanto; Ni made Marlin Minarsih; Lovany Marchelia Shafirarossa (Universitas Negeri Surabaya, 2026)
Nature-based learning offers opportunities to support the participation, development, and learning of children with disabilities; however, evidence regarding its forms, enabling conditions, and outcomes remains fragmented. This systematic literature review examined what existing literature reveals about nature-based learning experiences, participation, and developmental and educational outcomes for children with disabilities. Following the PRISMA framework, 15 studies were identified and synthesized from the selected literature. The studies represented diverse approaches, including Forest School, sensory gardens, horticultural activities, outdoor adventure, wild-nature experiences, and other forms of nature-based and outdoor learning. The synthesis generated three interconnected themes: diverse nature-based learning opportunities; accessibility and support as conditions for meaningful participation; and multidimensional developmental and educational outcomes. Across the studies, nature-based experiences provided opportunities for experiential and sensory learning, exploration, movement, autonomy, and social interaction, with reported outcomes spanning social participation, emotional well-being, sensory engagement, physical development, and learning. Importantly, the findings indicate that exposure to nature alone does not ensure positive outcomes. Rather, nature provides opportunities; accessibility and support enable meaningful participation; and meaningful participation creates pathways toward developmental and educational outcomes. The evidence remains predominantly focused on autistic children, highlighting the need for research involving a broader range of disabilities. These findings underscore the importance of designing accessible, supportive, and inclusive nature-based learning experiences that enable meaningful participation for diverse learners.